Vietnam:Past and Present, 4th edition - SarDesai, D.R. (Routledge, 2020)
“An indispensable tool for college students and general readers, the only available text that treats Vietnamese history in its entirety, from its beginning to the twenty-first century, as it places Vietnam within the regional and global context. SarDesai’s Vietnam looks at Vietnam as a country and not just as a war. The text has also benefited from its author’s decades-long expertise on Southeast Asia as reflected in the comprehensive bibliography and use of the latest works.” —NGUYEN THI DIEU, Ph.D., Temple University